Earthquake-Induced Hazards Modeling and Damage Mapping Using Computer Vision, Machine Learning, and Geospatial Data Analytics - Asadi, Adel. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Civil Engineering.; Advisor: Laurie Baise.; Committee: Babak Moaveni, Magaly Koch, Snehamoy Chatterjee, and Abani Patra.; Keywords: Civil engineering, Geological engineering, and Computer science.